Recent progress in solution processable organic light emitting devices - Choulis, Stelios A.; So, Franky; Krummacher, Benjamin C. (My University, 2007)
Organic light emitting devices (OLEDs) have been the subject of intense research because of their potential for flat panel display and solid state lighting applications. While small molecule OLEDs with very high efficiencies have been demonstrated, solution processable devices are more desirable for large size flat panel display and solid state applications because they are compatible with low cost, large area roll-to-roll manufacturing process. In this review paper, we will present the recent progress made in solution processable OLEDs. The paper will be divided into three parts. In the first part of the paper, we will focus on the recent development of fluorescent polymer OLEDs based on conjugated polyfluorene copolymers. Specifically, we will present results of carrier transport and injection measurements, and discuss how the charge transport and injection properties affect the device performance. In the second part of the paper, we will focus on the recent progress on phosphorescent dye-dispersed nonconjugated polymer OLEDs. Specifically, we will present our recent results on high efficiency green and blue emitting devices based on the dye-dispersed polymer approach. Similar to fluorescent conjugated polymer OLEDs, charge transport and injection properties in dye-dispersed polymer OLEDs also play an important role in the device performance. In the third part of this paper, we will present our results on white emitting phosphorescent OLEDs. Two approaches have been used to demonstrate white emitting OLEDs. First, white emitting OLEDs were made using blue emitting OLEDs with downconversion phosphors. Second, white emitting OLEDs were made by dispersing red, green, and blue phosphorescent dyes into the light emitting layer. High efficiency devices have been demonstrated with both approaches
Keywords: Copolymers; Flat panel displays; Polymers; Solid-state lasers